MIKROALBUMINURIA SEBAGAI PREDIKTOR LUARAN BURUK STROKE ISKEMIK AKUT DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR - Hesti Heptaningrum; I Made Oka Adnyana; Thomas Eko Purwata (NEURONA, 2020)
Introduction: Microalbuminuria is one of indicators for systemic endovascular damage related to endothelial damage and dysfunction. Microalbuminuria has become an important risk factor for predicting the risk and prognosis of cerebrovascular disease. However, its association with acute ischemic stroke remains unclear, particularly those related with other comorbidities. Aim: To address the role of microalbuminuria as a predictor of poor neurological outcome among patients with acute ischemic stroke at Sanglah Hospital Denpasar. Methods: This was a prospective cohort study involving acute ischemic stroke patients admitted at Sanglah Hospital Denpasar during October to December 2018. All patients who fulfilled inclusion and exclusion criteria and provided consent to participate in the study were included. Microalbuminuria was measured with albumin to creatinine ratio with concentration of 30–300mcg/mg. Stroke outcome was classified into either good or poor according to early and late National Institutes Health Stroke Scale (NIHSS) score (during patient’s admission and 7th day, respectively). Bivariate and multivariate statistical analyses were conducted. Results: Sixty patients were recruited. Microalbuminuria increased poor neurological outcome among stroke patients significantly (RR 5.47; 95% CI 2.17–13.8; p<0.001). Multivariate analysis demonstrated that microalbuminuria (RR=21.99; 95% CI 2.01-240.41; p=0.011), DM (RR=11.66; 95% CI 2.00–67.65; p=0.006), and dyslipidemia (RR 11.45; 95% CI 1.10–119.23; p=0.041) as an independent predictor of poor neurological outcome among acute ischemic stroke patients. Discussion: Therefore, microalbuminuria is consistently independent predictors of poor outcome in admitted acute ischemic stroke patients. Keywords: acute ischemic stroke, microalbuminuria, poor neurological outcome